Electrospinning of bilayer emulsions: The role of gum Arabic as a coating layer in the gelatin-stabilized emulsions. (September 2019) - Zhang, Cen; Li, Yang; Wang, Peng; Zhang, Aiping; Feng, Fengqin; Zhang, Hui
Abstract: In this work, the uniform core-shell nanofibers were fabricated by electrospinning of bilayer emulsions, which were formed by the addition of gum arabic with opposite charges into the gelatin-stabilized emulsions. The increased weight ratios of gum arabic enhanced the emulsion stability by progressively increasing the viscosity of bilayer emulsions, which contributed to the formation of bead-free and smooth electrospun fibers with the increasing diameters. Transmission electron microscopy and confocal laser scanning microscopy confirmed that corn oil was evenly distributed in the bilayer emulsion-based fibers. These fibers with various amounts of gum arabic showed a high thermal decomposition stability upon heating to 250 ° C, as hydrogen bonds played an important role in the binding of gum arabic to gelatin. The fiber mats showed high oil encapsulation efficiency and good storage stability during 5 days. These results may provide a new strategy to develop bilayer emulsion-based electrospun fibers for bioactive encapsulation in food applications. Graphical abstract: Image 1 Highlights: The uniform nanofibers were fabricated by bilayer emulsion electrospinning. The encapsulated oil was evenly distributed in the bilayer emulsion-based fibers. Hydrogen bonds played an important role in the binding of gum arabic to gelatin. These fibers showed high thermal decomposition stability and storage stability.